2021
DOI: 10.1093/cid/ciab1048
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) Breakthrough Infection and Post-Vaccination Neutralizing Antibodies Among Healthcare Workers in a Referral Hospital in Tokyo: A Case-Control Matching Study

Abstract: Background While increasing coverage of effective vaccines against coronavirus disease 2019 (COVID-19), emergent variants raise concerns about breakthrough infection. Data are limited, however, whether breakthrough infection during the epidemic of the variant is ascribed to insufficient vaccine-induced immunogenicity. Methods We described incident COVID-19 in relation to the vaccination program among workers of a referral hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 18 publications
2
50
3
1
Order By: Relevance
“…As of October 2021, we have completed three surveys, in each of which we measured anti‐SARS‐CoV‐2 nucleocapsid (all surveys) and spike (from the second survey onward) protein antibodies. The details of the study design are available elsewhere ( 9 ). For the present analysis, we used the data of the third survey (June 2021), 2 months after the in‐house vaccination program (COVID‐19 mRNA‐lipid nanoparticle BNT162b2; BioNTech, Pfizer [BioNTech SE, Mainz, Germany; Pfizer Inc., New York, New York]).…”
Section: Methodsmentioning
confidence: 99%
“…As of October 2021, we have completed three surveys, in each of which we measured anti‐SARS‐CoV‐2 nucleocapsid (all surveys) and spike (from the second survey onward) protein antibodies. The details of the study design are available elsewhere ( 9 ). For the present analysis, we used the data of the third survey (June 2021), 2 months after the in‐house vaccination program (COVID‐19 mRNA‐lipid nanoparticle BNT162b2; BioNTech, Pfizer [BioNTech SE, Mainz, Germany; Pfizer Inc., New York, New York]).…”
Section: Methodsmentioning
confidence: 99%
“…In general, it is not recommended to perform serological tests in order to determine whether the patient is protected [ 18 ]. Nevertheless, antibody levels are often used both in research and in clinical practice, and a correlation between higher antibody levels and neutralization of virus has been shown, though not in all studies [ 19 , 20 ]. We cannot provide any recommendation regarding use of serology to guide vaccination schedule in this review, and local guidelines on vaccination schedule should be followed.…”
Section: Immune Response To Vaccines In Hmmentioning
confidence: 99%
“… 6 However, severity of disease due to SARS-CoV-2 breakthrough infections and confounding risk factors for breakthrough infections were not compared between patients and controls. Other studies in healthy individuals observed associations between reduced humoral responses after SARS-CoV-2 vaccination and an increased incidence of SARS-CoV-2 breakthrough infections and possibly more severe disease, 7 , 8 , 9 but there is a paucity of data from patients with immune-mediated inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%